EFEKTIFITAS PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN KEMAMPUAN MEMBACA KATA PADA ANAK KESULITAN BELAJAR KELAS III di SDN 15 ULU GADUT - FITRIA HERMAN (Jurnal Penelitian Pendidikan Khusus, 2015)
This research in the wake of the problems that researchers have found in SD N 15 Ulu Gadut Padang, a third grade children learning disability who are having problems in reading the word. The ability to read the children is still very low, children are often wrong in reading the words contained digraphs letters "ng". Under these conditions, this study aims to prove the effectiveness of the scientific approach to improve the ability to read the word, in which the word is contained in the letter digraphs in children learning disability  X.   This research uses experimental approach in the form of Single Subject Research (SSR) with multiple baseline design cross variables. subjects were children learning disability class III. Results of the analysis of the conditions and showed a tendency towards inter-state, the tendency of stability, the tendency of trace data and increased levels of positive changes, as well as the percentage of overlap (overlapped data) on an analysis of conditions in the target behavior 1 is 0% and 50.1%, on the target behavior 2 is 0% and 50.1%, and the target behavior 3 0% and 50.1%. Overlape the smaller the percentage, the better the effective of interventions to change treatment. So it can be concluded that the scientific approach is effective in improving reading skills in children learning disability said X class III in SD N 15 Ulu Gadut Padang.         Keyword: Children learning disability : reading the word : scientific approach